A FOLLOW THE CROWD WITHOUT CONSIDERING WHY: PASSIVE FOLLOWERS IN ORGANIZATIONS - Sotiroska, Kalina (International Scientific Journal Vision, 2019)
The concept of followership, the identification of styles of followership styles and the structuring of power in follower-organized organizations are relatively new paradigms, as the point of view is that followership is an influential factor independent of leadership. This study is concentrate on passive followership style among employees in the organization. The main features of passive followers are listed. Lastly, the practical implications of moving from passive to exemplary followers are given.